M8 The influence of anatomy on prognosis of an aortic arch anomaly– a radiological view. (7th September 2020) - Ctori, Elena G; Crucean, Adrian; Pinkey, Benjamin; McGuirk, Simon; Anderson, Robert H; Stickley, John; Jones, Tim; Seale, Anna N
Abstract : Introduction: Due to the incorporation of the three vessel and trachea view to antenatal screening, understanding the prognosis of aortic arch anomalies (AAAs) is important. Certain morphological characteristics, detectable on cross-sectional imaging, may influence symptom development. This study aims to explore the radiological features of AAAs which may increase risk of symptomatic presentation and surgery. Methods: A retrospective observational study from a single cardiac surgical unit. Individuals with an AAA who underwent computed tomography/magnetic resonance imaging between 6/2014 and 9/2018 were included. Imaging studies were evaluated for arch morphology. In double aortic arches (DAA), arch patency was assessed. Presence of Kommerell diverticulum was noted in aberrant subclavian cases. The laterality of the arterial ligament was observed in those with a right aortic arch/mirrored branching. Case notes were reviewed to assess presence of vascular-ring symptoms and surgical intervention. Results: We identified 167 individuals. Of cases with aberrant subclavian, 24/79(30.4%) had a Kommerell. The infants with a Kommerell were more likely to be symptomatic (p≤0.001) and undergo surgery (p≤0.001). 55% of DAA patients had dual arch patency. Patency did not influence symptoms (p=0.396) or surgery (p=0.250). The arterial ligament was identified in 28/70(40%) of right arch/mirrored branching patients. Laterality did not influence symptom development (p=0.692). Conclusion: Infants with an aberrant subclavian and Kommerell have increased risk of symptoms/surgical intervention and should remain under monitoring. This study did not identify the arterial ligament insertion point in those with a right aortic arch/mirrored branching, which may be a useful prognostic tool. Better foetal imaging methods could help antenatal prediction.